Pengaruh Aplikasi Tik Tok Terhadap Minat Belajar Mahasiswa Fiikom Universitas Mercu Buana Yogyakarta Angkatan 2021 - Khotimah, Miftahul Khusnul; Adinda, Lili; Latif, Nursafika Azis Abd. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Advances in technology in the field of communication and information have led to changes and human development in various aspects of life. This research is entitled "The Effect of the TikTok Application on Learning Interests of Universitar Mercu Buana Yogyakarta Students Class of 2021". The purpose of this research is to find out whether the TikTok application has an influence on the learning interest of Mercu Buana University students in Yogyakarta. This research method uses quantitative research methods. The results of this study indicate that there is a positive influence of 85% between the use of the TikTok application and the learning interest of students at Mercu Buana University, Yogyakarta. It can be concluded that the higher the use of the TikTok application, it will affect student learning interest.